A non-metallic high-performance plate and preparation method thereof
By filling the polypropylene honeycomb board with composite epoxy resin and fiber aerogel, and combining the reinforced needle puncture parts for hot pressing and molding, the problem of easy softening and deformation of the sheet at high temperature is solved, and strength improvement and heat resistance and stability enhancement are achieved.
Patent Information
- Application Number
- CN202411513883.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing polypropylene honeycomb sandwich sheets are prone to softening and deforming at high temperatures, lack of strength and poor temperature resistance, resulting in short service life and high material cost.
The pretreated polypropylene honeycomb plate is used to fill with composite epoxy resin and fiber aerogel, and the reinforced needle puncture member is combined on both sides. The strength of the needle puncture member is enhanced by oxidation, carbonization and impregnation treatment, and then heat-pressure-curing and molding is carried out.
It effectively improves the strength and heat resistance of the board, maintains the excellent structural performance of the polypropylene honeycomb board, extends the service life and reduces the material cost.
Smart Images

Figure CN119017807B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of non-metallic sheet materials, and in particular to a non-metallic high-performance sheet material and a preparation method thereof. Background Art
[0002] At present, polypropylene honeycomb panels have the characteristics of light weight, high strength, water resistance, heat insulation, sound insulation, etc., and are particularly suitable for making various composite sandwich panels. Existing polypropylene honeycomb sandwich panels are mostly made of polypropylene honeycomb and glass fiber. Although they have good toughness, they are insufficient in strength and are prone to warping and deformation.
[0003] With the development of modern science and technology, new materials are constantly being developed, produced and widely used. At present, carbon fiber composite materials have been widely used due to their high specific strength, large specific modulus, good durability and small thermal expansion coefficient.
[0004] The existing technology is to impregnate carbon fiber with resin and then laminate and solidify it. Due to the chemical inertness and high crystallinity of polypropylene material, it is difficult to bond with carbon fiber. High-density panels have poor temperature resistance, low interlayer peeling strength, easy delamination, short service life, and frequent replacement leads to high material costs.
[0005] Epoxy resin can be directly used as the core of carbon fiber reinforced composite materials, but epoxy resin has a high density and the thermal deformation temperature of polypropylene is lower than the molding temperature of epoxy resin, resulting in the prepared board not only having high density and heavy weight, but also the board structure being difficult to control after high-temperature molding, which needs to be solved urgently. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a non-metallic high-performance plate and a preparation method.
[0007] A non-metallic high-performance plate material comprises: a pretreated polypropylene honeycomb panel and reinforced needle-punched parts combined on both sides of the pretreated honeycomb panel; the pretreated polypropylene honeycomb panel is a polypropylene honeycomb panel filled with composite epoxy resin and fiber aerogel; the reinforced needle-punched parts are obtained by laying fiber aerogel, carbon fiber fabric, fiber aerogel, and carbon fiber fabric on the surface of carbon fiber fabric in sequence, then needle-punching, then oxidizing and carbonizing, and then dipping with composite epoxy resin.
[0008] Preferably, the fiber aerogel is prepared by the following specific operation: adding 1,4-butanediol diglycidyl ether to a sodium hydroxide solution and stirring evenly, adding microcrystalline cellulose and polyvinyl alcohol and stirring for 1-2 hours, adding tin tetrachloride and graphene oxide in sequence, continuing to stir until a wet gel is formed, standing for 1-2 days, washing with water, and freeze-drying.
[0009] More preferably, the mass ratio of 1,4-butanediol diglycidyl ether, microcrystalline cellulose, polyvinyl alcohol, tin tetrachloride and graphene oxide is 1-10:10-20:1-2:0.1-1:1-5.
[0010] More preferably, the freeze-drying temperature is -30 to -40°C.
[0011] Preferably, the composite epoxy resin comprises: a premixed epoxy resin and a composite curing agent, and the mass ratio of the premixed epoxy resin to the composite curing agent is 10:2-4.
[0012] More preferably, the premixed epoxy resin is prepared by the following specific operation: bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether are mixed and stirred at 40-50° C. for 10-20 minutes; wherein the mass ratio of bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether is 10-20:1-5:1-2.
[0013] More preferably, the composite curing agent is obtained by mixing isophorone diamine, ethylene diamine, and curing accelerator DMP-30 in a mass ratio of 1.5-2.5:1-2.5:0.5-1.
[0014] Preferably, in the pretreated polypropylene honeycomb panel, the mass ratio of the composite epoxy resin to the fiber aerogel is 11-15:1-2.
[0015] Preferably, in the reinforced needle-punched part, the mass ratio of the carbon fiber fabric to the fiber aerogel is 10:1-4.
[0016] Preferably, the carbon fiber fabric is a non-weft unidirectional fabric with a surface density of 200-300 g / m 2 .
[0017] Preferably, the oxidation treatment temperature is 200-215° C., and the oxidation treatment time is 5-15 min; the carbonization treatment temperature is 1000-1200° C., and the carbonization treatment time is 1-2 min.
[0018] The method for preparing the above-mentioned non-metallic high-performance plate comprises the following steps:
[0019] S1. Place a polypropylene honeycomb panel in a mold, crush the fiber aerogel, mix it with the composite epoxy resin, and evenly inject it into the holes of the polypropylene honeycomb panel, let it stand at 40-50° C. for 10-20 minutes, and cool it to obtain a pretreated polypropylene honeycomb panel;
[0020] S2. Lay the reinforced needle-punched parts on both sides of the pre-treated honeycomb panel, heat-press and solidify them at 15-22MPa, and cool them to room temperature.
[0021] Preferably, during the hot pressing curing process, the temperature is adjusted to 60-70° C. and kept for 1-2 hours, and then raised to 120-150° C. and kept for 10-20 minutes.
[0022] Beneficial Effects
[0023] The present invention adopts microcrystalline cellulose, polyvinyl alcohol and graphene oxide to prepare wet gel, and then freeze-drying, so that the obtained fiber aerogel is not only light in weight and low in density, but also has high mechanical strength. The fiber aerogel and composite epoxy resin are then compounded and filled with polypropylene honeycomb panels, which not only makes the fiber aerogel and composite epoxy resin have good mutual dispersion performance, but also can effectively protect the polypropylene honeycomb panel from softening and deformation at high temperatures, effectively maintains the original excellent structural performance of the honeycomb panel, and the obtained pre-treated honeycomb panel has the characteristics of light weight, high strength and excellent aging resistance.
[0024] The present invention lays the fiber aerogel on the carbon fiber fabric, and then lays the carbon fiber fabric, the fiber aerogel, and the carbon fiber fabric in sequence, and after needle-punching, the fibers are better bonded to each other, and after oxidation and carbonization treatment, the bending and tensile strengths of the needle-punched parts are greatly enhanced under the premise of reducing the density of the needle-punched parts; and after being impregnated with glue, it is compounded with the pretreated honeycomb board and hot-pressed and cured to form an integrated structure of the internal glue layer, thereby ensuring the stability of the multi-layer structure. At the same time, the polypropylene honeycomb board can retain its excellent performance, cooperate with the surface enhancement needle-punched parts, and have high heat resistance and stability and are not easy to delaminate under the premise of effective weight reduction.
[0025] The present invention can effectively retain the geometric structure of the polypropylene honeycomb panel, and at the same time has high interlayer shear strength. Even if it is placed in a high temperature environment for a long time, the mechanical strength of the material can be guaranteed, and the aging resistance is excellent. It has extremely good mechanical properties, weight reduction and stability, and is widely used in external load-bearing structures and interior secondary load-bearing structures. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a comparison chart of the tensile strength and interlaminar shear strength of the plates obtained in Example 5 and Comparative Examples 1-2.
[0027] Figure 2 It is a comparison chart of the bending strength and bending modulus of the plates obtained in Example 5 and Comparative Examples 1-2.
[0028] Figure 3 This is a comparison chart of the tensile strength retention rate, interlaminar shear strength retention rate and bending strength retention rate of the plates obtained in Example 5 and Comparative Examples 1-2 after thermal oxidation aging. DETAILED DESCRIPTION
[0029] The present invention will be further explained below in conjunction with specific embodiments.
[0030] The carbon fiber fabric used below is a non-weft unidirectional carbon fiber fabric purchased from a certain Bang (Shanghai) Industrial Co., Ltd., and its surface density is 300g / m 2 .
[0031] The polypropylene honeycomb panel used below was purchased from Jiangsu Quanmou New Materials Co., Ltd. It has a height of 12±1.5 mm, a wall thickness of 0.5±0.1 mm, and a circular honeycomb aperture of 5±0.5 mm.
[0032] Embodiment 1:
[0033] A non-metal high-performance plate comprises: a pre-treated polypropylene honeycomb plate and reinforced needle-punched parts combined on both sides of the pre-treated honeycomb plate.
[0034] The pretreated polypropylene honeycomb panel is a polypropylene honeycomb panel filled with composite epoxy resin and fiber aerogel; wherein the mass ratio of the composite epoxy resin to the fiber aerogel is 11:1.
[0035] The fiber aerogel was prepared by the following specific operation: 1 kg of 1,4-butanediol diglycidyl ether was added to 60 kg of 0.5 mol / L sodium hydroxide solution and stirred evenly, 10 kg of microcrystalline cellulose and 1 kg of polyvinyl alcohol were added, and stirred at a speed of 1000 r / min for 1 hour, 0.1 kg of tin tetrachloride and 1 kg of graphene oxide were added in sequence, and stirring was continued until a wet gel was formed, and the mixture was allowed to stand for 1 day, washed with deionized water, and freeze-dried at a temperature of -30°C.
[0036] The composite epoxy resin includes: premixed epoxy resin and composite curing agent, and the mass ratio of premixed epoxy resin and composite curing agent is 5:1. The premixed epoxy resin is prepared by the following specific operation: bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether are mixed, stirred at 40°C for 10 minutes, and the stirring speed is 100r / min. Among them, the mass ratio of bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether is 10:1:1. The composite curing agent is obtained by mixing isophorone diamine, ethylenediamine, and curing accelerator DMP-30 in a mass ratio of 1.5:1:0.5.
[0037] The reinforced needle-punched parts are prepared by the following specific operations: fiber aerogel, carbon fiber fabric, fiber aerogel, and carbon fiber fabric are laid on the surface of the carbon fiber fabric in sequence, and then needle-punched to obtain a needle-punched part with a thickness of 5-12 mm, and the mass ratio of carbon fiber fabric to fiber aerogel is 10:1; then sent to a muffle furnace, oxidized in an air atmosphere for 5 minutes, and the oxidation temperature is 200°C; then nitrogen is introduced, carbonized in a full nitrogen atmosphere for 1 minute, and the carbonization temperature is 1000°C, and then cooled to room temperature; sent to a vacuum impregnation bag, and the composite epoxy resin is injected into the vacuum impregnation bag for impregnation treatment.
[0038] The method for preparing the above-mentioned non-metallic high-performance plate comprises the following steps:
[0039] S1. Place a polypropylene honeycomb panel in a mold, crush the fiber aerogel, mix it with the composite epoxy resin, and evenly inject it into the holes of the polypropylene honeycomb panel. Let it stand at 40° C. for 10 minutes, take it out after cooling, and trim it to obtain a pretreated polypropylene honeycomb panel.
[0040] S2. Lay the reinforced needle-punched parts on both sides of the pretreated honeycomb panel, place them in a hot press for curing and molding, adjust the temperature to 60°C for 1 hour, increase the temperature to 120°C for 10 minutes, maintain the pressure at 15MPa during the hot press curing and molding process, and cool to room temperature.
[0041] Embodiment 2:
[0042] A non-metal high-performance plate comprises: a pre-treated polypropylene honeycomb plate and reinforced needle-punched parts combined on both sides of the pre-treated honeycomb plate.
[0043] The pretreated polypropylene honeycomb panel is a polypropylene honeycomb panel filled with composite epoxy resin and fiber aerogel; wherein the mass ratio of the composite epoxy resin to the fiber aerogel is 15:2.
[0044] The fiber aerogel was prepared by the following specific operation: 10 kg of 1,4-butanediol diglycidyl ether was added to 100 kg of 1.2 mol / L sodium hydroxide solution and stirred evenly, 20 kg of microcrystalline cellulose and 2 kg of polyvinyl alcohol were added, and stirred at a speed of 2000 r / min for 2 h, 1 kg of tin tetrachloride and 5 kg of graphene oxide were added in sequence, and stirring was continued until a wet gel was formed, and the mixture was allowed to stand for 2 days, washed with deionized water, and freeze-dried at a temperature of -40°C.
[0045] The composite epoxy resin includes: premixed epoxy resin and composite curing agent, and the mass ratio of premixed epoxy resin and composite curing agent is 5:2. The premixed epoxy resin is prepared by the following specific operation: bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether are mixed, stirred at 50°C for 20 minutes, and the stirring speed is 500r / min. Among them, the mass ratio of bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether is 20:5:2. The composite curing agent is obtained by mixing isophorone diamine, ethylenediamine, and curing accelerator DMP-30 in a mass ratio of 2.5:2.5:1.
[0046] The reinforced needle-punched parts are prepared by the following specific operations: fiber aerogel, carbon fiber fabric, fiber aerogel, and carbon fiber fabric are laid on the surface of the carbon fiber fabric in sequence, and then needle-punched to obtain a needle-punched part with a thickness of 5-12 mm, and the mass ratio of carbon fiber fabric to fiber aerogel is 5:2; then sent to a muffle furnace, oxidized in an air atmosphere for 15 minutes, and the oxidation temperature is 215°C; then nitrogen is introduced, carbonized in a full nitrogen atmosphere for 2 minutes, and the carbonization temperature is 1200°C, and then cooled to room temperature; sent to a vacuum impregnation bag, and the composite epoxy resin is injected into the vacuum impregnation bag for impregnation treatment.
[0047] The method for preparing the above non-metallic high-performance plate comprises the following steps:
[0048] S1. Place a polypropylene honeycomb panel in a mold, crush the fiber aerogel, mix it with the composite epoxy resin, and evenly inject it into the holes of the polypropylene honeycomb panel. Let it stand at 50° C. for 20 minutes, take it out after cooling, and trim it to obtain a pretreated polypropylene honeycomb panel.
[0049] S2. Lay the reinforced needle-punched parts on both sides of the pretreated honeycomb panel, place them in a hot press for curing and molding, adjust the temperature to 70°C for 2 hours, increase the temperature to 150°C for 20 minutes, maintain the pressure at 22MPa during the hot press curing and molding process, and cool to room temperature.
[0050] Embodiment 3:
[0051] A non-metal high-performance plate comprises: a pre-treated polypropylene honeycomb plate and reinforced needle-punched parts combined on both sides of the pre-treated honeycomb plate.
[0052] The pretreated polypropylene honeycomb panel is a polypropylene honeycomb panel filled with composite epoxy resin and fiber aerogel; wherein the mass ratio of the composite epoxy resin to the fiber aerogel is 12:1.7.
[0053] The fiber aerogel was prepared by the following specific operation: 3 kg of 1,4-butanediol diglycidyl ether was added to 90 kg of 0.6 mol / L sodium hydroxide solution and stirred evenly, 18 kg of microcrystalline cellulose and 1.3 kg of polyvinyl alcohol were added, and stirred at a speed of 1800 r / min for 80 min, 0.7 kg of tin tetrachloride and 2 kg of graphene oxide were added in sequence, and stirring was continued until a wet gel was formed, and the mixture was allowed to stand for 1.5 days, washed with deionized water, and freeze-dried at a temperature of -37°C.
[0054] The composite epoxy resin includes: premixed epoxy resin and composite curing agent, and the mass ratio of premixed epoxy resin and composite curing agent is 4:1. The premixed epoxy resin is prepared by the following specific operation: bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether are mixed, stirred at 48°C for 12 minutes, and the stirring speed is 400r / min. Among them, the mass ratio of bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether is 12:4:1.3. The composite curing agent is obtained by mixing isophorone diamine, ethylenediamine, and curing accelerator DMP-30 in a mass ratio of 2.2:1.5:0.8.
[0055] The reinforced needle-punched parts are prepared by the following specific operations: fiber aerogel, carbon fiber fabric, fiber aerogel, and carbon fiber fabric are laid on the surface of the carbon fiber fabric in sequence, and then needle-punched to obtain a needle-punched part with a thickness of 5-12 mm, and the mass ratio of carbon fiber fabric to fiber aerogel is 5:1; then sent to a muffle furnace, oxidized in an air atmosphere for 12 minutes, and the oxidation temperature is 205°C; then nitrogen is introduced, carbonized in a full nitrogen atmosphere for 1.8 minutes, and the carbonization temperature is 1050°C, and then cooled to room temperature; sent to a vacuum impregnation bag, and the composite epoxy resin is injected into the vacuum impregnation bag for impregnation treatment.
[0056] The method for preparing the above-mentioned non-metallic high-performance plate comprises the following steps:
[0057] S1. Place a polypropylene honeycomb panel in a mold, crush the fiber aerogel, mix it with the composite epoxy resin, and evenly inject it into the holes of the polypropylene honeycomb panel. Let it stand at 47° C. for 12 minutes, take it out after cooling, and trim the edges to obtain a pretreated polypropylene honeycomb panel.
[0058] S2. Lay the reinforced needle-punched parts on both sides of the pretreated honeycomb panel, place them in a hot press for curing and molding, adjust the temperature to 66°C for 80 minutes, increase the temperature to 140°C for 12 minutes, maintain the pressure at 21MPa during the hot press curing and molding process, and cool to room temperature.
[0059] Embodiment 4:
[0060] A non-metal high-performance plate comprises: a pre-treated polypropylene honeycomb plate and reinforced needle-punched parts combined on both sides of the pre-treated honeycomb plate.
[0061] The pretreated polypropylene honeycomb panel is a polypropylene honeycomb panel filled with composite epoxy resin and fiber aerogel; wherein the mass ratio of the composite epoxy resin to the fiber aerogel is 14:1.3.
[0062] The fiber aerogel was prepared by the following specific operation: 7 kg of 1,4-butanediol diglycidyl ether was added to 70 kg of 1 mol / L sodium hydroxide solution and stirred evenly, 12 kg of microcrystalline cellulose and 1.7 kg of polyvinyl alcohol were added, and stirred at a speed of 1200 r / min for 100 min, 0.3 kg of tin tetrachloride and 4 kg of graphene oxide were added in sequence, and stirring was continued until a wet gel was formed, and the mixture was allowed to stand for 1.5 days, washed with deionized water, and freeze-dried at a temperature of -33°C.
[0063] The composite epoxy resin includes: premixed epoxy resin and composite curing agent, and the mass ratio of premixed epoxy resin and composite curing agent is 2:0.7. The premixed epoxy resin is prepared by the following specific operation: bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether are mixed, stirred at 42°C for 18 minutes, and the stirring speed is 200r / min. Among them, the mass ratio of bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether is 18:2:1.7. The composite curing agent is obtained by mixing isophorone diamine, ethylenediamine, and curing accelerator DMP-30 in a mass ratio of 0.9:1:0.3.
[0064] The reinforced needle-punched parts are prepared by the following specific operations: fiber aerogel, carbon fiber fabric, fiber aerogel, and carbon fiber fabric are laid on the surface of the carbon fiber fabric in sequence, and then needle-punched to obtain a needle-punched part with a thickness of 5-12 mm, and the mass ratio of carbon fiber fabric to fiber aerogel is 10:3; then sent to a muffle furnace, oxidized in an air atmosphere for 8 minutes, and the oxidation temperature is 210°C; then nitrogen is introduced, carbonized in a full nitrogen atmosphere for 1.2 minutes, and the carbonization temperature is 1150°C, and then cooled to room temperature; sent to a vacuum impregnation bag, and the composite epoxy resin is injected into the vacuum impregnation bag for impregnation treatment.
[0065] The method for preparing the above non-metallic high-performance plate comprises the following steps:
[0066] S1. Place a polypropylene honeycomb panel in a mold, crush the fiber aerogel, mix it with the composite epoxy resin, and inject it into the holes of the polypropylene honeycomb panel. Let it stand at 43° C. for 18 minutes, take it out after cooling, and trim it to obtain a pretreated polypropylene honeycomb panel.
[0067] S2. Lay the reinforced needle-punched parts on both sides of the pretreated honeycomb panel, place them in a hot press for curing and molding, adjust the temperature to 64°C for 100 minutes, increase the temperature to 130°C for 18 minutes, maintain the pressure at 17MPa during the hot press curing and molding process, and cool to room temperature.
[0068] Embodiment 5:
[0069] A non-metal high-performance plate comprises: a pre-treated polypropylene honeycomb plate and reinforced needle-punched parts combined on both sides of the pre-treated honeycomb plate.
[0070] The pretreated polypropylene honeycomb panel is a polypropylene honeycomb panel filled with composite epoxy resin and fiber aerogel; wherein the mass ratio of the composite epoxy resin to the fiber aerogel is 13:1.5.
[0071] The fiber aerogel was prepared by the following specific operation: 5 kg of 1,4-butanediol diglycidyl ether was added to 80 kg of 0.8 mol / L sodium hydroxide solution and stirred evenly, 15 kg of microcrystalline cellulose and 1.5 kg of polyvinyl alcohol were added, and stirred at a speed of 1500 r / min for 90 min. 0.5 kg of tin tetrachloride and 3 kg of graphene oxide were added in sequence, and stirring was continued until a wet gel was formed. The mixture was allowed to stand for 1.5 days, washed with deionized water, and freeze-dried at a temperature of -35°C.
[0072] The composite epoxy resin includes: premixed epoxy resin and composite curing agent, and the mass ratio of premixed epoxy resin and composite curing agent is 10:3. The premixed epoxy resin is prepared by the following specific operation: bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether are mixed, stirred at 43°C for 15 minutes, and the stirring speed is 300r / min. Among them, the mass ratio of bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether is 15:3:1.5. The composite curing agent is obtained by mixing isophorone diamine, ethylenediamine, and curing accelerator DMP-30 in a mass ratio of 2:1.8:0.7.
[0073] The reinforced needle-punched parts are prepared by the following specific operations: fiber aerogel, carbon fiber fabric, fiber aerogel, and carbon fiber fabric are laid on the surface of the carbon fiber fabric in sequence, and then needle-punched to obtain a needle-punched part with a thickness of 5-12 mm, and the mass ratio of carbon fiber fabric to fiber aerogel is 4:1; then sent to a muffle furnace, oxidized in an air atmosphere for 10 minutes, and the oxidation temperature is 208°C; then nitrogen is introduced, carbonized in a full nitrogen atmosphere for 1.5 minutes, and the carbonization temperature is 1100°C, and then cooled to room temperature; sent to a vacuum impregnation bag, and the composite epoxy resin is injected into the vacuum impregnation bag for impregnation treatment.
[0074] The method for preparing the above non-metallic high-performance plate comprises the following steps:
[0075] S1. Place a polypropylene honeycomb panel in a mold, crush the fiber aerogel, mix it with the composite epoxy resin, and inject it into the holes of the polypropylene honeycomb panel. Let it stand at 45° C. for 15 minutes, take it out after cooling, and trim it to obtain a pretreated polypropylene honeycomb panel.
[0076] S2. Lay the reinforced needle-punched parts on both sides of the pretreated honeycomb panel, place them in a hot press for curing and molding, adjust the temperature to 65°C for 90 minutes, increase the temperature to 135°C for 15 minutes, maintain the pressure at 19 MPa during the hot press curing and molding process, and cool to room temperature.
[0077] Comparative Example 1:
[0078] A non-metal high-performance plate comprises: a pre-treated polypropylene honeycomb plate and reinforced needle-punched parts combined on both sides of the pre-treated honeycomb plate.
[0079] The pretreated polypropylene honeycomb panel is a polypropylene honeycomb panel filled with composite epoxy resin and fiber aerogel; wherein the mass ratio of the composite epoxy resin to the fiber aerogel is 13:1.5.
[0080] The fiber aerogel was prepared by the following specific operation: 5 kg of 1,4-butanediol diglycidyl ether was added to 80 kg of 0.8 mol / L sodium hydroxide solution and stirred evenly, 15 kg of microcrystalline cellulose and 1.5 kg of polyvinyl alcohol were added, and stirred at a speed of 1500 r / min for 90 min, 0.5 kg of tin tetrachloride was added and continued to stir until a wet gel was formed, and the mixture was allowed to stand for 1.5 days, washed with deionized water, and freeze-dried at a temperature of -35°C.
[0081] The composite epoxy resin includes: premixed epoxy resin and composite curing agent, and the mass ratio of premixed epoxy resin and composite curing agent is 10:3. The premixed epoxy resin is prepared by the following specific operation: bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether are mixed, stirred at 43°C for 15 minutes, and the stirring speed is 300r / min. Among them, the mass ratio of bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether is 15:3:1.5. The composite curing agent is obtained by mixing isophorone diamine, ethylenediamine, and curing accelerator DMP-30 in a mass ratio of 2:1.8:0.7.
[0082] The reinforced needle-punched parts are prepared by the following specific operations: fiber aerogel, carbon fiber fabric, fiber aerogel, and carbon fiber fabric are laid on the surface of the carbon fiber fabric in sequence, and then needle-punched to obtain a needle-punched part with a thickness of 5-12 mm, and the mass ratio of carbon fiber fabric to fiber aerogel is 4:1; then sent to a muffle furnace, oxidized in an air atmosphere for 10 minutes, and the oxidation temperature is 208°C; then nitrogen is introduced, carbonized in a full nitrogen atmosphere for 1.5 minutes, and the carbonization temperature is 1100°C, and then cooled to room temperature; sent to a vacuum impregnation bag, and the composite epoxy resin is injected into the vacuum impregnation bag for impregnation treatment.
[0083] The method for preparing the above-mentioned non-metallic high-performance plate comprises the following steps:
[0084] S1. Place a polypropylene honeycomb panel in a mold, crush the fiber aerogel, mix it with the composite epoxy resin, and inject it into the holes of the polypropylene honeycomb panel. Let it stand at 45° C. for 15 minutes, take it out after cooling, and trim it to obtain a pretreated polypropylene honeycomb panel.
[0085] S2. Lay the reinforced needle-punched parts on both sides of the pretreated honeycomb panel, place them in a hot press for curing and molding, adjust the temperature to 65°C for 90 minutes, increase the temperature to 135°C for 15 minutes, maintain the pressure at 19 MPa during the hot press curing and molding process, and cool to room temperature.
[0086] Comparative Example 2:
[0087] A non-metal high-performance plate comprises: a pre-treated polypropylene honeycomb plate and reinforced needle-punched parts combined on both sides of the pre-treated honeycomb plate.
[0088] The pretreated polypropylene honeycomb panel is a polypropylene honeycomb panel filled with composite epoxy resin and fiber aerogel; wherein the mass ratio of the composite epoxy resin to the fiber aerogel is 13:1.5.
[0089] The fiber aerogel was prepared by the following specific operation: 5 kg of 1,4-butanediol diglycidyl ether was added to 80 kg of 0.8 mol / L sodium hydroxide solution and stirred evenly, 15 kg of microcrystalline cellulose and 1.5 kg of polyvinyl alcohol were added, and stirred at a speed of 1500 r / min for 90 min. 0.5 kg of tin tetrachloride and 3 kg of graphene oxide were added in sequence, and stirring was continued until a wet gel was formed. The mixture was allowed to stand for 1.5 days, washed with deionized water, and freeze-dried at a temperature of -35°C.
[0090] The composite epoxy resin includes: premixed epoxy resin and composite curing agent, and the mass ratio of premixed epoxy resin and composite curing agent is 10:3. The premixed epoxy resin is prepared by the following specific operation: bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether are mixed, stirred at 43°C for 15 minutes, and the stirring speed is 300r / min. Among them, the mass ratio of bisphenol A epoxy resin, nano-silicon dioxide, and 1,4-butanediol glycidyl ether is 15:3:1.5. The composite curing agent is obtained by mixing isophorone diamine, ethylenediamine, and curing accelerator DMP-30 in a mass ratio of 2:1.8:0.7.
[0091] The reinforced needle-punched parts are prepared by the following specific operations: fiber aerogel, carbon fiber fabric, fiber aerogel, and carbon fiber fabric are laid on the surface of the carbon fiber fabric in sequence, and then needle-punched to obtain a needle-punched part with a thickness of 5-12 mm, and the mass ratio of carbon fiber fabric to fiber aerogel is 4:1; the parts are sent into a vacuum impregnation bag, and the composite epoxy resin is injected into the vacuum impregnation bag for impregnation treatment.
[0092] The method for preparing the above non-metallic high-performance plate comprises the following steps:
[0093] S1. Place a polypropylene honeycomb panel in a mold, crush the fiber aerogel, mix it with the composite epoxy resin, and inject it into the holes of the polypropylene honeycomb panel. Let it stand at 45° C. for 15 minutes, take it out after cooling, and trim it to obtain a pretreated polypropylene honeycomb panel.
[0094] S2. Lay the reinforced needle-punched parts on both sides of the pretreated honeycomb panel, place them in a hot press for curing and molding, adjust the temperature to 65°C for 90 minutes, increase the temperature to 135°C for 15 minutes, maintain the pressure at 19 MPa during the hot press curing and molding process, and cool to room temperature.
[0095] The tensile strength of the plates obtained in Example 5 and Comparative Examples 1-2 was measured with reference to GB / T 1447-2005 "Test method for tensile properties of fiber reinforced plastics"; the interlaminar shear strength of the plates obtained in Example 5 and Comparative Examples 1-2 was measured with reference to JC / T 773-2010 "Determination of interlaminar shear strength of fiber reinforced plastics by short beam method".
[0096] like Figure 1 As shown, the tensile strength and interlaminar shear strength of the plate obtained in Example 5 are the highest, which are better than those of the plates obtained in Comparative Examples 1-2 (P < 0.05).
[0097] The bending strength and bending modulus of the plates obtained in Example 5 and Comparative Examples 1-2 were measured with reference to GB / T 1449-2005 “Test method for bending properties of fiber reinforced plastics”.
[0098] like Figure 2 As shown, the bending strength and bending modulus of the plate obtained in Example 5 are the highest, which are better than those of the plates obtained in Comparative Examples 1-2 (P < 0.05).
[0099] The plates obtained in Example 5 and Comparative Examples 1-2 were placed in a forced air constant temperature oven at a constant temperature of 150°C for heat aging for 504 hours. After being taken out and cooled to room temperature, the tensile strength, interlaminar shear strength and bending strength of the samples in each group after thermal oxidative aging were measured again according to the above-mentioned detection method, and the strength retention rate after thermal oxidative aging was calculated.
[0100] Strength retention rate = tensile strength after thermal oxidation aging / interlaminar shear strength / bending strength ÷ original tensile strength / interlaminar shear strength / bending strength × 100%
[0101] like Figure 3 As shown, the strength retention rates of the plates obtained in Example 5 are the highest, and are better than those of the plates obtained in Comparative Examples 1-2 (P < 0.05).
[0102] The applicant believes that this is because, on the one hand, the present invention adopts microcrystalline cellulose, polyvinyl alcohol and graphene oxide to prepare wet gel, and then freeze-drying, so that the obtained fiber aerogel is not only light in weight and low in density, but also has high mechanical strength; and then the fiber aerogel and the composite epoxy resin are compounded to fill the polypropylene honeycomb panel, which not only makes the fiber aerogel and the composite epoxy resin have good mutual dispersion performance, but also can effectively protect the polypropylene honeycomb panel from softening and deformation at high temperature, effectively maintain the original excellent structural performance of the honeycomb panel, and at the same time the obtained pretreated honeycomb panel has the characteristics of light weight, high strength and excellent aging resistance. On the other hand, the present invention lays the fiber aerogel on the carbon fiber fabric, and then lays the carbon fiber fabric, the fiber aerogel, and the carbon fiber fabric in sequence, which are better bonded to each other after needle punching, and then after oxidation and carbonization treatment, the bending and tensile strength of the needle-punched part is greatly enhanced under the premise of reducing the density of the needle-punched part; and after being impregnated with glue, it is compounded with the pretreated honeycomb board and hot-pressed and cured to form an integrated structure of the internal glue layer, thereby ensuring the stability of the multi-layer structure. At the same time, the polypropylene honeycomb board can retain its excellent performance, cooperate with the surface enhancement needle-punched part, and have high heat resistance and stability and is not easy to delaminate under the premise of effective weight reduction.
[0103] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A non-metallic high-performance sheet material, characterized in that: include: A pre-treated polypropylene honeycomb panel and a reinforcing needle punched member bonded to both sides of the pre-treated honeycomb panel; The pretreated polypropylene honeycomb panel is a polypropylene honeycomb panel filled with composite epoxy resin and fiber aerogel; The mass ratio of composite epoxy resin to fiber aerogel is 11-15:1-2; The composite epoxy resin comprises: a premixed epoxy resin and a composite curing agent, wherein the mass ratio of the premixed epoxy resin to the composite curing agent is 10:2-4; The premixed epoxy resin is prepared by the following specific operation: bisphenol A epoxy resin, nano silicon dioxide, and 1,4-butanediol glycidyl ether are mixed, and stirred at 40-50° C. for 10-20 minutes; wherein the mass ratio of bisphenol A epoxy resin, nano silicon dioxide, and 1,4-butanediol glycidyl ether is 10-20:1-5:1-2; The composite curing agent is obtained by mixing isophorone diamine, ethylenediamine and curing accelerator DMP-30 in a mass ratio of 1.5-2.5:1-2.5:0.5-1; The reinforced needle-punched parts are obtained by laying fiber aerogel, carbon fiber fabric, fiber aerogel, and carbon fiber fabric on the surface of carbon fiber fabric in sequence, and then needle-punching, and then oxidizing and carbonizing them, and then using composite epoxy resin for dipping. The fiber aerogel was prepared by the following specific operation: 1,4-butanediol diglycidyl ether was added to a sodium hydroxide solution and stirred evenly, microcrystalline cellulose and polyvinyl alcohol were added and stirred for 1-2 hours, tin tetrachloride and graphene oxide were added in sequence, stirring was continued until a wet gel was formed, the gel was allowed to stand for 1-2 days, washed with water, and freeze-dried at -30 to -40°C; The mass ratio of 1,4-butanediol diglycidyl ether, microcrystalline cellulose, polyvinyl alcohol, tin tetrachloride and graphene oxide is 1-10:10-20:1-2:0.1-1:1-5.
2. The non-metallic high-performance sheet material according to claim 1, characterized in that: In the reinforced needle-punched parts, the mass ratio of carbon fiber fabric to fiber aerogel is 10:1-4.
3. The non-metallic high-performance plate material according to claim 1, characterized in that: Carbon fiber fabric is a non-weft unidirectional fabric with a surface density of 200-300g / m 2 .
4. The non-metallic high-performance sheet material according to claim 1, characterized in that: The oxidation treatment temperature is 200-215°C, and the oxidation treatment time is 5-15 minutes; the carbonization treatment temperature is 1000-1200°C, and the carbonization treatment time is 1-2 minutes.
5. A method for preparing a non-metallic high-performance plate, applicable to a non-metallic high-performance plate as claimed in any one of claims 1 to 4, characterized in that: The steps include: S1. Place a polypropylene honeycomb panel in a mold, crush the fiber aerogel, mix it with the composite epoxy resin, and evenly inject it into the holes of the polypropylene honeycomb panel, let it stand at 40-50° C. for 10-20 minutes, and cool it to obtain a pretreated polypropylene honeycomb panel; S2, laying the reinforced needle-punched parts on both sides of the pre-treated honeycomb panel, hot pressing and curing at 15-22MPa, and cooling to room temperature; During the hot pressing curing process, adjust the temperature to 60-70℃ and keep it for 1-2 hours, then increase the temperature to 120-150℃ and keep it for 10-20 minutes.
Citation Information
Patent Citations
Preparation method of cellulose nanocrystal / graphene / polyvinyl alcohol aerogel
CN108579626A
Cellulose / graphene composite high-strength carbon fiber aerogel plate and preparation method thereof
CN113321523A
Honeycomb sandwich combined material board
CN205395290U